2018
DOI: 10.2478/ace-2018-0018
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Multi-Ribbed One-Way Composite Slabs Made of Steel Fibre, Foam, and Normal Concrete

Abstract: This paper aims to study the effect of reinforcement configuration (steel fibre and rebar) on the mechanical performance of composite slabs of the same total steel contents. We manufactured four pieces of fullscale multi-ribbed composite prefabricated slabs with different reinforcement configurations by using steel fibrereinforced concrete, foam concrete, and normal concrete. The multi-ribbed composite prefabricated slab has many excellent properties, such as light weight, good thermal and sound insulation. Th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 18 publications
0
6
0
Order By: Relevance
“…The bottom reinforcement of the beam around the slab contains six rebars having a diameter of 16 mm and stirrups made of bars with a diameter of 8 mm and the spacing of 250 mm. The tank was deflected by 17.8 mm/m in the south-east direction, and therefore it was rectified [20]. For that purpose, stacks of concrete blocks were pressed into the ground under reinforced concrete beams which were part of the foundation.…”
Section: Description Of the Tank And Its Rectificationmentioning
confidence: 99%
See 2 more Smart Citations
“…The bottom reinforcement of the beam around the slab contains six rebars having a diameter of 16 mm and stirrups made of bars with a diameter of 8 mm and the spacing of 250 mm. The tank was deflected by 17.8 mm/m in the south-east direction, and therefore it was rectified [20]. For that purpose, stacks of concrete blocks were pressed into the ground under reinforced concrete beams which were part of the foundation.…”
Section: Description Of the Tank And Its Rectificationmentioning
confidence: 99%
“…6c). Stiffness 𝑘 jack determined during the tests [20] was constant and equal to 105 MN/m. Stiffness 𝑘 fou of the foundation depended on the length of the concrete block stacks pressed into the ground.…”
Section: Research Programmementioning
confidence: 99%
See 1 more Smart Citation
“…Wang et al [7] investigated the effect of reinforcement configuration on the mechanical performance of composite slab containing both steel fiber and rebar. The slab composed of foam concrete as the core layer, steel fiber-reinforced concrete as the surficial layer, and rebar-reinforced concrete as the ribs.…”
Section: Overview Of Research In Ribbed Slabmentioning
confidence: 99%
“…Besides, in the study of Allawi and Jabir [42], slab moment capacities increased and displacement values decreased as a result of the use of crossties in voided slabs. Wang et al [43], has observed that the slab strength and displacement capacities increase when steel fiber reinforced concrete is used.…”
Section: Introductionmentioning
confidence: 99%